2011
DOI: 10.1017/s1368980010003782
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns, food and macronutrient intakes among adults in three ethnic groups in rural Kenya

Abstract: Objective: To compare dietary patterns and food and macronutrient intakes among adults in three ethnic groups in rural Kenya. Design: In the present cross-sectional study, dietary intake was estimated in adult volunteers using two non-consecutive interactive 24 h recalls. Dietary patterns were assessed from the number of meals and snacks per day and from the food items and major food groups registered, and their contribution to energy intake (EI) was calculated. Anthropometric values were measured and sociodem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 18 publications
5
36
0
1
Order By: Relevance
“…Women's dietary diversity indicators were also lower in Korogocho and were in line with previous findings [63]. Ethnicity was not included in the questions to avoid potential sensitivity but it should be explored in the future since dietary practices and patterns have been observed to differ among ethnic groups [64]. A double burden of malnutrition was identified among women, and better nutrition of the woman and child assessed seemed to be associated within households.…”
Section: Womensupporting
confidence: 83%
“…Women's dietary diversity indicators were also lower in Korogocho and were in line with previous findings [63]. Ethnicity was not included in the questions to avoid potential sensitivity but it should be explored in the future since dietary practices and patterns have been observed to differ among ethnic groups [64]. A double burden of malnutrition was identified among women, and better nutrition of the woman and child assessed seemed to be associated within households.…”
Section: Womensupporting
confidence: 83%
“…These findings are relatively similar to other studies among non-displaced men in rural Kenya (30,31) . This is in contrast with literature in other regions which has suggested that IDP generally have poorer nutritional status than surrounding, comparable non-displaced populations (32)(33)(34) .…”
Section: Discussionsupporting
confidence: 91%
“…It is clear that specific cultural groups or geographical areas within each country have varying degrees of vulnerability to food insecurity that may influence childhood nutritional status. One study of dietary intake patterns of three ethnic groups in Kenya (Luo, Kamba, and Maasai) found that the Maasai and Kamba were vulnerable to food insecurity compared to the Luo [34]. Specifically, the prevalence of underweight, a key indicator of food insecurity, was 13.7% for the Luo, 20.5% for the Kamba, and 24.2% for the Maasai [34].…”
Section: Discussionmentioning
confidence: 99%
“…One study of dietary intake patterns of three ethnic groups in Kenya (Luo, Kamba, and Maasai) found that the Maasai and Kamba were vulnerable to food insecurity compared to the Luo [34]. Specifically, the prevalence of underweight, a key indicator of food insecurity, was 13.7% for the Luo, 20.5% for the Kamba, and 24.2% for the Maasai [34]. Regarding maternal autonomy, the more independent a mother is to makes decisions related to health care, education, food, and have an independent source of income , the more likely her children are to be properly nourished [3538].…”
Section: Discussionmentioning
confidence: 99%